Bi-quadratic magnetoelectric coupling in underdoped La2CuO4+x - Panagopoulos, Christos (2013)
The recent discovery of relaxor ferroelectricity and magnetoelectric effect in lightly doped cuprate material La2CuO4+x has provided a number of questions concerning its theoretical description. Using a Ginzburg–Landau free energy approach, it has been argued that the magnetoelectric effect can be explained by bi-quadratic interaction terms in the free energy. Here, by using the same free energy functional, we study the variety of behavior which can emerge in the electric polarization under an external magnetic field. Subsequently, we discuss the role of Dzyaloshinskii–Moriya interaction in generating this magnetoelectric response. This work is particularly relevant for such relaxor systems where the material-dependent parameters would be affected by changes in, e.g., chemical doping or cooling rate.